Ibuprofen exposure in early neonatal life does not affect renal function in young adolescence. Issue 2 (14th June 2017) - Raaijmakers, Anke; Zhang, Zhen-Yu; Levtchenko, Elena; Simons, Sinno HP; Cauwenberghs, Nicholas; Heuvel, Lambertus P van den; Jacobs, Lotte; Staessen, Jan A; Allegaert, Karel
Abstract : Introduction: Ibuprofen exposure results in acute transient renal dysfunction in preterm neonates, but we are unaware of data on long-term renal safety. Methods: In a previously studied cohort of extreme low birth weight (ELBW, <1000 g) cases, the PREMATurity as predictor of children's Cardiovascular-renal Health study generated data on renal function (renal length, estimated glomerular filtration rate based on cystatin C (eGFRcysC ) at the age of 11 years. This data set in 93 ELBW cases may also generate data on long-term drug safety on ibuprofen. In this post hoc analysis, we linked markers of renal function in young adolescence in ELBW cases with their perinatal (prenatal maternal, setting at birth, treatment modalities including drug prescription during neonatal stay, neonatal creatinine values, postdischarge growth) characteristics, including but not limited to ibuprofen exposure during neonatal stay. Results: Ibuprofen exposure was not associated with significant differences in renal length or eGFRcysC . Moreover, we were unable to identify any other risk factor (perinatal characteristics, postnatal creatinine trends, postdischarge growth) on renal outcome in this cohort. Conclusions: Neonatal exposure to ibuprofen did not affect renal function. Larger studies are needed to explore the confounders of variability in renal function in former ELBW cases. This matters since ELBW relates to risk for hypertension, cardiovascular events and renal disease in later life and identification of risk factors holds the promise of secondary prevention. Trial registration number: NCT02147457.